Peningkatan Pengetahuan Remaja Putri Melalui Pendidikan Kesehatan Media Video tentang Bahaya Pernikahan Dini untuk Mencegah Stunting - Jafar, Sitti Rusdianah; Mawaddah, Ely; Mardiatun, Mardiatun; Sri Puja Warnis W, Gusti Ayu; Rahmatillah, Febry Dwi (Poltekkes Kemenkes Mataram, 2025)
Indonesia is currently experiencing a major nutritional problem, namely stunting. Children who are born with short stature or not in accordance with the standards for their age are called stunting. This is caused by growth and development disorders in children due to chronic nutritional problems caused by malnutrition for a long time. This study aims to determine the effect of health education about the dangers of early marriage through videos to prevent stunting on the level of knowledge of adolescent girls. The design of this study used a pre-experimental method with the One Group Pretest and Posttest Design approach. The sampling technique used Purposive Sampling with 100 respondents. Statistical analysis used a non-parametric test, namely the Wilcoxon Signed Rank Test. The results of the study showed a change in the level of knowledge before and after being given a video of the dangers of early marriage to prevent stunting. Thus, it can be concluded that there is an effect of health education through videos of the dangers of early marriage to prevent stunting on the level of knowledge of adolescent girls at SMKN 1 Narmada. It is recommended that readers use this study as a source of information and an appeal in prevention so as not to get married early as an effort to prevent stunting.